THE ANALYSIS ON THE CHLORINE CONTENTS IN RICE CIRCULATION IN PASAR BESAR OF MALANG AS THE BIOLOGICAL LEARNING RESOURCE - Dewi Rosita; Siti Zaenab; Moch. Agus Krisno Budianto (JPBI (Jurnal Pendidikan Biologi Indonesia), 2016)
This research aimed to investigate the chlorine contents in rice circulation in Pasar Besar of which findings were supposed to be applicable as Biological learning resource. This research was officially conducted at March 29 – April 6 2016 in Putra Indonesia Malang Laboratory. This research was of descriptively quantitative design since the main aim of this research was to describe the chlorine contents in rice. The sampling technique engaging regarding this research was purposive sampling with two repetitions in total. The sample of rice that was going to be analyzed was originally from Pasar Besar comprised 19 types (considering the brands), they were: Piala, Mentari, Padi Wangi, Bintang Biru, Rosita Super, Kancil, Bintang Mas, Bulan Mas, Puteri,  Lombok, Maknyus, Apel, Manggis, Mangga, Cucak Rowo, Beras Padi, Raja Boga dan Monas. In addition, the methods accommodated in terms of testing the reaction included testing the color reaction test, testing the iodometric titration, and measuring the average percentage of chlorine contents in the whole sample.  Moreover, this research revealed that the 19 types sample of rice taken from Pasar Besar is 0 % or negative of chlorine contents. Consequently, they were safe to consume.